Characteristics of Corticospinal Tract Area According to Pontine Level - Seo, Jeong Pyo (Yonsei University College of Medicine, 2013)
Diffusion tensor imaging (DTI) allows to isolate the corticospinal tract (CST) area from adjacent structures. Using DTI, we investigated the characteristics of the CST areas according to the pontine level in the normal human brain. We recruited 33 healthy subjects and DTIs were acquired using a sensitivity-encoding head coil on a 1.5-T Philips Gyroscan Intera. We measured the size and fractional anisotropy (FA) value of the CST area at the upper, middle, and lower pons. The size of the CST area in the lower pons was smaller than those of the mid-pons and upper pons, and the size of the CST area in the mid-pons was smallerthan that of the upper pons (p<0.05). FA values of the lower pons were larger than those of the mid-pons and upper pons, and the FA value of the mid-pons was also larger than that of the upper pons (p<0.05). In summary, we found a smaller size and higher FA value of the CST area from rostral to caudal direction in the pons. These results suggest a more compact neural structure of CST areas from rostral to caudal direction in the pons.